Implementasi Model Point-Counter-Point (PCP) pada Hasil Belajar Siswa Materi Getaran dan Gelombang - Ratih Mayang Sari; Effendi Effendi; Wahid Gunarto; Siti Anisatur Rofiqoh; Haresda Varrentine Rohim (Pendidikan Fisika Universitas Nurul Huda, 2020)
This research is motivated by the low learning outcomes of 8th grade students of SMP Negeri 5 Madang Suku I. So, the researchers examined the influence of Cooperative Learning Model Point-Counter-Point Type (PCP) on students’ learning outcomes in learning materials Vibration and Waves. With the aim to determine the effect of Point-Counter-Point Cooperative Learning model (PCP) on students’ learning outcomes. The sampling technique in this study was done by random sampling. The experimental class used PCP learning model while the control class used Lecture method. Data collection techniques using written tests and hypothesis testing using the T test. Based on the test results, obtained an average score of the experimental class is 70.22 and the average score of the control class is 63.28, so it can be seen that there is a significant influence on students’ learning outcomes.